The Dynamics of Immigrant Welfare and Labor Market Behavior - Jörgen Hansen; Magnus Lofstrom (Institute for the Study of Labor (IZA), 2001)
This paper analyzes transitions into and out of 3 different labor market states, social assistance, unemployment and employment. We estimate a dynamic multinomial logit model, controlling for endogenous initial condition and unobserved heterogeneity, using a large representative Swedish panel data set, LINDA, for the years 1990 to 1996. The unadjusted data indicates that immigrants are more likely to receive both social assistance and unemployment compensation than natives. Immigrants are less likely to remain employed in consecutive years than natives and are more likely to stay on welfare and to receive unemployment insurance in a year, given participation in the previous year. The empirical results suggest that refugee immigrants display a greater degree of ?structural? state dependence than natives. Further, immigrants from nonrefugee countries display a similar degree of ?structural? state dependence as natives. The high welfare participation rates among refugee immigrants seem to be due to the existence of a ?welfare trap?, while participation among natives and non-refugee immigrants is largely due to permanent unobserved characteristics. These results suggest that welfare reforms will have differential effects on refugee immigrants and natives.
Keywords: I38; J61; J15; I30; J18; 330; Welfare; labor market behavior; transition; immigration; state dependence; Ausländische Arbeitskräfte; Sozialhilfeempfänger; Arbeitsmarkt; Arbeitslosigkeit; Soziale Sicherung; Schweden